"Tiers of Delay": Warfarin, Hip Fractures, and Target-Driven Care. (September 2014) - Eardley, W. G. P.; Macleod, K. E.; Freeman, H.; Tate, A.
Anticoagulation reversal is a common cause of operative delay. We sought to establish for the first time the impact this has on best practice tariff (BPT) for patients with hip fracture admitted on warfarin. All patients with hip fracture treated operatively over a 32-month period were reviewed. Basic demographics, time to theater, length of stay, and mortality were recorded for all patients. Independent samples t -tests were used to identify statistically significant differences between patients on warfarin and those not taking the drug. A total of 83 patients were admitted anticoagulated with a mean international normalized ratio of 2.65 and a median time to theater of 49.7 hours. Of these patients, 79% breached BPT, incurring significant financial loss. In the control group, 908 patients took a median 24.5 hours, a 28% breach of BPT ( P < .01). Length of stay, Nottingham Hip Fracture Score, and predicted 30-day mortality were similar for both the groups. As well as affecting clinical outcome following hip fracture, delay due to anticoagulation causes considerable loss of BPT. Potential loss of revenue due to delays over the study period was £80 000, inspiring the establishment of an "early trigger" anticoagulation protocol. Although it is accepted that there are limitations to this work, it should raise awareness of the real impact of warfarin on patients with hip fracture both in terms of outcome and for the first time, loss of potential revenue.